Synthesising Resource-Advantage and Hofstede Cultural Dimensions: Customer Orientation, Knowledge Creation and Firm Performance - Melissa Li Sa Liow (Centre For Tourism Planning and Development, 2021)
There is a dearth of studies on synthesising the resource-advantage theory and Hofstedecultural dimensions that explore the influence of customer orientation and knowledgecreation on the firm performance for small hotels. This paper reviews extant literaturethat provides insights on the influence of customer orientation and knowledge creationon firm performance. In-depth interviews with three hotel owners and three hotelmanagers were performed in this study. The results disclose that forging memorableand positive customer experiences and developing informed knowledge databases arebusiness practices that sustain the firm performance. From the theoretical aspect, it is apreliminary step to blend the culturally relevant customer orientation and knowledgecreation elements into forming a firm performance framework designed for small hotels.